2016
DOI: 10.1016/j.ijfoodmicro.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the bacterial community in directly brined Aloreña de Málaga table olive fermentations by metagenetic analysis

Abstract: This study uses an "omics" approach to evaluate the bacterial biodiversity changes during fermentation process of natural green cracked Aloreña de Málaga table olives, from raw material to fermented fruit. For this purpose, two industries separated by almost 20km in Guadalhorce Valley (Málaga, Spain) were analysed for obtaining both brines and fruit samples at different moments of fermentation (0, 7, 30 and 120days). Physicochemical and microbial counts during fermentation showed the typical evolution of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
4
42
1
Order By: Relevance
“…In this work, the microbial populations of the olives which received a heat treatment consisted mainly of Lactobacillus and Pediococcus . In contrast, Medina et al (2016) , using pyrosequencing analysis, reported the presence of undesirable Celerinatantimonas, Pseudomonas , and Propionibacterium as the most abundant genera detected in traditional industrially fermented fruits while the species of the Lactobacillaceae family were in low proportion (3–8%). This work also reveals information about the bacterial biodiversity for CA and FG Aloreña de Málaga denominations, whose alpha-biodiversity indexes and number of OTUs obtained in the present work were considerably higher than in previous studies ( Medina et al, 2016 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this work, the microbial populations of the olives which received a heat treatment consisted mainly of Lactobacillus and Pediococcus . In contrast, Medina et al (2016) , using pyrosequencing analysis, reported the presence of undesirable Celerinatantimonas, Pseudomonas , and Propionibacterium as the most abundant genera detected in traditional industrially fermented fruits while the species of the Lactobacillaceae family were in low proportion (3–8%). This work also reveals information about the bacterial biodiversity for CA and FG Aloreña de Málaga denominations, whose alpha-biodiversity indexes and number of OTUs obtained in the present work were considerably higher than in previous studies ( Medina et al, 2016 ).…”
Section: Discussionmentioning
confidence: 93%
“…Microbial genomic DNA from olive and brine samples at the end of the fermentation process (138 days) was extracted as described by Medina et al (2016) and sent to the Sequencing and Bioinformatic Service of FISABIO (Valencia, Spain) for bacterial metagenomic analysis. 16S rDNA gene amplicons were amplified following the 16S rDNA gene Metagenomic Sequencing Library Preparation Illumina protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen species of Pseudomonas were identified from this genus in total (Table S2), with most identified as non‐infectious species, except for Pseudomonas oryzihabitans that was detected in sample W2, in a proportion of 0.03%. This genus has previously been shown to be dominant in Korean kimchi, ‘Jiaozi’, brined table olive, Pu‐erh tea, and ‘doubanjiang‐meju’, which is an anaerobic fermentation food derived from broad beans. Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the application of autochthonous strains has arisen to face consumers' demand for more traditional products with a unique sensory profile and peculiar organoleptic properties [60]. Autochthonous strains, being well adapted to the raw material conditions, can easily lead the fermentation process by dominating the table olives microenvironment [3,51].…”
Section: Table Olives' Starter Culturesmentioning
confidence: 99%